The Unification of Quranic Recitations: A Historical Analysis and Its Impact on The Preservation of The Usmanic Manuscript - Muizzul Haq Anwar; Andi Miswar; Halimah Basri (TAFASIR: Journal of Quranic Studies, 2026)
This study analyzes the historical background of Quranic recitation unification during the reign of Caliph Uthmān bin ‘Affān and its significant impact on textual preservation. The expansion of Islamic territory led to various dialectal differences (sab’atu ahruf) that potentially caused communal division among Muslims. Utilizing a library research method with a historical-analytical approach, this study finds that the unification initiated by Uthmān was not merely an administrative policy but a crucial socio-religious strategy to maintain the authenticity of the revelation. The results indicate that the standardization into the Uṡmānic Mushaf successfully prevented textual alterations and provided a definitive legal framework for the science of Qira'at in subsequent periods. Consequently, this unification ensured the stability of Quranic transmission across generations and regions.